Job Control and Employee Innovative Behavior: A Moderated Mediation Model - Zhao, Guolong; Luan, Yuxiang; Ding, He; Zhou, Zixiang (Frontiers in Psychology, 2022)
The purpose of this paper is to investigate the relationship between job control (JC) and employee innovative behavior (EIB). Basing on self-determination theory(SDT), we put a moderated mediation model that tested the mediating effect of creative self-efficacy(CSE) and moderating effect of mindfulness（MF）. 329 samples came from Internet companies were used to test our hypotheses. We found that JC was positively related to EIB via CSE. Moreover, MF moderated the relationship between JC and EIB and the mediating role of CSE. The contributions and limitations were discussed.